β1- and β2-adrenergic receptor mediated spontaneous contractions and ryanodine receptor channel opening in human failing heart - Weilan Mo; Nicole A. Beard; Katherine T. Gillette-Browne; Karen Hay; Elizabeth Cheesman; Alexander Dashwood; Melanie Spratt; Annalese B. Semmler; Yee Weng Wong; Haris Haqqani; Derek R. Laver; Torsten Christ; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
In heart failure, β-adrenergic receptor (β-AR)-Gsα-cAMP-protein kinase A (PKA) signalling predisposes to delayed-afterdepolarisation-mediated arrhythmias. Phosphodiesterases (PDEs) hydrolyse cAMP, and PDE3 restrains β 1 -AR, β 2 -AR-mediated inotropic responses in failing hearts from β-blocker-treated patients. Whether these receptors provoke arrhythmias through ryanodine receptor (RyR2) dysregulation, and how PDE activity and prior β-blockade treatment modify this, is undefined. We sought to define how β 1 -AR and β 2 -AR activation provokes arrhythmias through RyR2 mechanisms in explanted human failing hearts, and how PDE activity and prior β-blocker therapy modulate this response. A diastolic model of ventricular arrhythmia using human right ventricular trabeculae with pacing stopped was used. Trabeculae were exposed to (-)-noradrenaline/(-)-adrenaline to activate β 1 -AR/β 2 -AR respectively with or without PDE inhibitors and monitored for spontaneous contractions. In parallel, sarcoplasmic reticulum vesicles from trabeculae were used to assess RyR2 channel function, phosphorylation and oxidation. Activation of β 1 -AR or β 2 -AR increased the frequency of spontaneous contractions, concomitant increases in diastolic RyR2 channel opening, phosphorylation and oxidation. Trabeculae from carvedilol-treated patients showed fewer β 2 -AR-mediated spontaneous contractions than those treated with β 1 -AR blockers. The PDE3 inhibitor cilostamide augmented β 2 -AR-mediated spontaneous contractions, RyR2 channel opening and Ser2808 phosphorylation. In human failing heart, β 1 -AR or β 2 -AR activation increased arrhythmic contractions associated with greater diastolic RyR2 channel opening, phosphorylation and oxidation. PDE3 attenuated β 2 -AR-mediated arrhythmic contractions, RyR2 channel opening and Ser2808 hyperphosphorylation. These findings suggest that combining β 1 - and β 2 -AR blockade with strategies that reduce RyR2 Ca 2+ leak and preserve RyR2-associated PDE3 activity may improve arrhythmia control in heart failure. Graphical abstract The arrhythmogenic human failing heart. Figure shows β 1 -AR, β 2 -AR mediated arrhythmia mechanisms in human HF. Activated β 1 -AR or β 2 -AR couple to the Gsα-protein-adenylyl cyclase signalling pathway to increase cyclic AMP, activation of PKA with consequent phosphorylation of RyR2. Other changes to RyR2 include oxidation and dissociation of FKBP12.6 (Walweel et al. 2017; Denniss et al. 2020). The changes contribute to Ca 2+ leak from the sarcoplasmic reticulum through RyR2 during diastole to cause outward transport of Ca 2+ /inward transport of Na + through the Na + /Ca 2+ exchanger resulting in DAD induced action potentials, depolarization of the myocyte and arrhythmic contractions (Walweel et al. 2017; Denniss et al. 2020). The β 2 -AR pathway that mediates arrhythmia generation is under the control of PDE3 (this paper).

Mycoplasma mycoides subspecies capri, an uncommon mastitis and respiratory pathogen isolated in a German flock of goats - Henrik Wagner; Martin Heller; Ahmad Fawzy; Christiane Schnee; Anne Nesseler; Ute Kaim; Christa Ewers; Torsten Semmler; Joachim Spergser; Tilman Schultze; Tobias Eisenberg (Veterinary Microbiology, 2024)

A dominant clonal lineage of Streptococcus uberis in cattle in Germany - Linda Fenske; Irene Noll; Jochen Blom; Christa Ewers; Torsten Semmler; Ahmad Fawzy; Tobias Eisenberg (Antonie van Leeuwenhoek, 2022)
Bovine mastitis causes enormous economic losses in the dairy industry with Streptococcus uberis as one of the most common bacterial pathogens causing clinical and subclinical variations. In most cases mastitis can be cured by intramammary administration of antimicrobial agents. However, the severity of the clinical manifestations can vary greatly from mild to severe symtoms. In this study, a comparative genomic analysis of 24 S. uberis isolates from three dairy farms in Germany, affected by different courses of infection was conducted. While there were sporadic mild infections in farm A and B, a large number of infections were observed within a very short period of time in farm C. The comparison of virulence genes, antimicrobial resistance genes and prophage regions revealed no features that might be responsible for this severe course. However, almost all isolates from farm C showed the same, novel MLST profile (ST1373), thus a clonal outbreak cannot be excluded, whereby the actual reason for the particular virulence remains unknown. This study demonstrates the importance of extensive metagenomic studies, including the host genomes and the environment, to gain further evidence on the pathogenicity of S. uberis .

Relatedness of wildlife and livestock avian isolates of the nosocomial pathogen Acinetobacter baumannii to lineages spread in hospitals worldwide - Gottfried Wilharm; Evelyn Skiebe; Paul G. Higgins; Marie T. Poppel; Ulrike Blaschke; Sarah Leser; Christine Heider; Magdalena Heindorf; Paul Brauner; Udo Jäckel; Karin Böhland; Christiane Cuny; et al. (Environmental Microbiology, 2017)
Summary The natural habitats and potential reservoirs of the nosocomial pathogen Acinetobacter baumannii are poorly defined. Here, we put forth and tested the hypothesis of avian reservoirs of A . baumannii . We screened tracheal and rectal swab samples from livestock (chicken, geese) and wild birds (white stork nestlings) and isolated A . baumannii from 3% of sampled chicken ( n = 220), 8% of geese ( n = 40) and 25% of white stork nestlings ( n = 661). Virulence of selected avian A . baumannii isolates was comparable to that of clinical isolates in the Galleria mellonella infection model. Whole genome sequencing revealed the close relationship of an antibiotic‐susceptible chicken isolate from Germany with a multidrug‐resistant human clinical isolate from China and additional linkages between livestock isolates and human clinical isolates related to international clonal lineages. Moreover, we identified stork isolates related to human clinical isolates from the United States. Multilocus sequence typing disclosed further kinship between avian and human isolates. Avian isolates do not form a distinct clade within the phylogeny of A . baumannii , instead they diverge into different lineages. Further, we provide evidence that A . baumannii is constantly present in the habitats occupied by storks. Collectively, our study suggests A . baumannii could be a zoonotic organism that may disseminate into livestock.